Establishing a best fit model of finger length to occlusal vertical dimension among students of college of health sciences Bayero University Kano - Ikusika OF; Idon PI; Iwuchukwu AO; Zirra AF; Usman N (Ibom Medical Journal)
Background: Anthropometric measurements like finger lengths may shorten the time taken for occlusal vertical dimension (OVD) estimation in the edentulous. They have sparingly been studied in Nigerian populations.